2004
DOI: 10.1074/jbc.m402299200
|View full text |Cite
|
Sign up to set email alerts
|

ERK1/2 Regulates Intracellular ATP Levels through α-Enolase Expression in Cardiomyocytes Exposed to Ischemic Hypoxia and Reoxygenation

Abstract: Extracellular signal-regulated kinase 1/2 (ERK1/2) is known to function in cell survival in response to various stresses; however, the mechanism of cell survival by ERK1/2 remains poorly elucidated in ischemic heart. Here we applied functional proteomics by two-dimensional electrophoresis to identify a cellular target of ERK1/2 in response to ischemic hypoxia. Approximately 1500 spots were detected by Coomassie Brilliant Blue staining of a sample from unstimulated cells. The staining intensities of at least 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
74
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(78 citation statements)
references
References 67 publications
4
74
0
Order By: Relevance
“…Previous studies demonstrated that mitochondrial dysfunction with energy depletion causes cell death (33,34) and that tau abnormalities alone can cause neurodegenerative diseases (35,36), indicating that each pathway can independently cause neuronal death. However, previous studies showed that there is a correlation between ATP level and the activity of tau kinases including MAPK/ERK1/2 (37,38). These results enable us to assume that mitochondrial dysfunction with a decreased ATP level and the enhancement of tau phosphorylation synergistically contribute to neurodegeneration in aged NPC1ϩ/Ϫ mouse brains.…”
Section: Figmentioning
confidence: 64%
“…Previous studies demonstrated that mitochondrial dysfunction with energy depletion causes cell death (33,34) and that tau abnormalities alone can cause neurodegenerative diseases (35,36), indicating that each pathway can independently cause neuronal death. However, previous studies showed that there is a correlation between ATP level and the activity of tau kinases including MAPK/ERK1/2 (37,38). These results enable us to assume that mitochondrial dysfunction with a decreased ATP level and the enhancement of tau phosphorylation synergistically contribute to neurodegeneration in aged NPC1ϩ/Ϫ mouse brains.…”
Section: Figmentioning
confidence: 64%
“…Numerous reports indicate that the ERK1/2 signaling pathway plays an important role in cardiovascular physiology and pathology, such as cardiac hypertrophy [29], myocyte proliferation [30], endothelial cell proliferation [31], and vascular smooth muscle cells proliferation and migration [32,33], especially in myocardial ischemic-reperfusion injury [13,34,35]. However, little is known about the role of the ERK1/2 signaling pathway in CME.…”
Section: Discussionmentioning
confidence: 99%
“…While some studies show that ERK1/2 signaling provides beneficial, cardioprotective effects on certain cardiac pathological processes, such as ischemia and reperfusion [13,14,15,16,17], growing evidence indicates that ERK1/2 is also involved in cardiovascular inflammation [18,19,20]. However, it remains unknown whether ERK1/2 plays a role in CME.…”
Section: Introductionmentioning
confidence: 99%
“…This separation is characterized by the use of a hydrophilic stationary phase, that is, cyano-, diol-, amino-and other bonded phases [18], and a hydrophobic organic mobile phase [19]. The elution step occurs by increasing the polarity of the mobile phase, normally by performing a water gradient resulting in an order of elution inverted relative to RPLC [19,20], that is, the less polar peptides elute first and the more polar peptides elute later. HILIC has also been found to allow enrichment and the targeted ana lysis of posttranslational modifications, such as glycosylation, N-acetylation and phosphorylation, in proteomics applications [19].…”
Section: Hydrophilic Interaction Liquid Chromatographymentioning
confidence: 99%